Study on survival mechanisms of circulating tumor cells and identification of metastatic biomarkers for breast cancer - Fu, Afu (2016)
Breast cancer remains curable until the metastatic cancer cells disseminate beyond the regional lymph nodes. The 5-year relative survival rate of stage IV breast cancer is less than 22%. Therefore, strategies to prevent the dissemination of breast cancer cells into bloodstream, eliminate the circulating tumor cells (CTCs), or suppress the proliferation of disseminated tumor cells (DTCs), can potentially inhibit cancer progression and improve the survival of breast cancer patients. So far, the mechanisms of how hemodynamic shear force induces apoptosis of CTCs and how metastatic breast cancer cell manage to survive in blood circulation are still unclear. Therefore, this thesis focused on the survival mechanisms of CTCs and aims to identify functional biomarkers and develop therapeutic strategies for metastatic breast cancer.